Omaraki: Dementia therapy facilities in Malang with a therapeutic architecture approach - Rayanjani, Muhammad Fairuz Zaki (Maliki Interdisciplinary Journal, 2024)
Dementia poses a global health challenge, with over 50 million cases worldwide in 2020, projected to reach 152 million by 2050. In Indonesia, dementia cases are rising sharply, expected to triple by 2050. Malang City, with a significant elderly population, urgently needs dementia therapy facilities. This study proposes OMARAKI, a therapeutic architecture approach to designing dementia therapy facilities in Malang City. OMARAKI integrates passive elements like familiar settings and active therapies such as cognitive exercises and artistic activities. By optimizing lighting, air quality, and green spaces, OMARAKI aims to enhance patient well-being, reduce symptoms of anxiety and depression, and promote social engagement. This initiative not only addresses immediate healthcare needs but also supports sustainable dementia care solutions in Indonesia, emphasizing holistic support for patients and families.